On the intercultural sensitivity of university students in multicultural regions: A case study in Macao - Chen, Hong; Hu, Bo (Frontiers in Psychology, 2023)
Intercultural sensitivity has been regarded as a very important ability necessary for living in multicultural countries and regions. In this research, the quantitative method was used to explore the intercultural sensitivity of university students in Macao, a typical multicultural region in China. By adopting the Intercultural Sensitivity Scale developed by Chen & Starosta (2000) and a sociodemographic questionnaire designed by the authors, this study investigated the intercultural sensitivity level of university students in Macao, and explored whether there were any significant differences in student groups in terms of gender, grade, program (language of instruction adopted in a major), courses related to intercultural communication, overseas experience, and foreign language proficiency. The findings of the study on a sample of 375 participants showed that university students in Macao had a relatively high intercultural sensitivity level. There were significant differences in different student groups in terms of gender, grade, courses related to intercultural communication, and foreign language proficiency. This study has implications for both educational policy makers and educators and can ultimately help university students in a multicultural environment improve their intercultural sensitivity and sustainable development.